Microlearning Videos to Foster Cyberbullying Understanding and Digital Empathy in Vocational Education: A Mixed-Methods Study - Putri, Kharisma Rosyiana; Budianto, Aris; Efendi, Agus (The Indonesian Institute of Science and Technology Research, 2026)
The rapid advancement of digital technology has transformed students’ learning behavior and online interaction, increasing the risk of cyberbullying among adolescents. This study analyzed vocational high school students’ understanding of the forms of cyberbullying through microlearning-based educational videos. A mixed-method sequential explanatory design was employed, integrating quantitative (one-group pretest–posttest) and qualitative (semi-structured interviews) approaches. Participants included 35 tenth-grade students from a vocational high school in Surakarta. Quantitative data were analyzed using inferential statistics and Normalized Gain (N-Gain), and qualitative data were analyzed thematically. The results showed a significant difference between pretest and posttest scores (p = 0.010; t = -2.722; df = 34), with an N-Gain of 0.0804, categorized as low. A per-aspect analysis further indicated improvements across most cyberbullying aspects, particularly harassment, cyberstalking, flaming, and elimination, while impersonation remained relatively stable. Qualitative findings revealed that students were able to translate, interpret, and apply concepts related to cyberbullying after watching the videos, indicating improved comprehension and ethical awareness. The study concludes that microlearning-based educational videos contributed to measurable yet modest improvements in conceptual understanding and digital empathy among vocational students. The novelty of this research lies in combining microlearning principles with video-based media to strengthen cyberbullying awareness and digital ethics education in vocational learning contexts.